2019
DOI: 10.1175/jas-d-18-0365.1
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Directional Absorption of Orographic Gravity Waves and Its Impact on the Atmospheric General Circulation Simulated by the Weather Research and Forecasting Model

Abstract: In this work, a new parameterization scheme is developed to account for the directional absorption of orographic gravity waves (OGWs) using elliptical mountain-wave theory. The vertical momentum transport of OGWs is addressed separately for waves with different orientations through decomposition of the total wave momentum flux (WMF) into individual wave components. With the new scheme implemented in the Weather Research and Forecasting (WRF) Model, the impact of directional absorption of OGWs on the general ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…The present study focuses exclusively on the characteristics of OGWs at the surface (i.e., at the OGW source). Once generated, OGWs will propagate upward and affect the large-scale mean atmospheric circulation through transport of wave momentum [19]. In the context of climate change, will the propagation of parameterized OGWs also change in response to TP warming?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study focuses exclusively on the characteristics of OGWs at the surface (i.e., at the OGW source). Once generated, OGWs will propagate upward and affect the large-scale mean atmospheric circulation through transport of wave momentum [19]. In the context of climate change, will the propagation of parameterized OGWs also change in response to TP warming?…”
Section: Discussionmentioning
confidence: 99%
“…Non-local effects of OGWs over the TP have also been found [16,17], using the Met Office Unified Model (MetUM) and the European Centre for Medium-Range Weather Forecasts (ECMWF) Integrated Forecasting System (IFS), and can affect the wind circulation and precipitation in the Northern Hemisphere at timescales ranging from days to seasons. For example, changes in the parameterized OGWs over the TP were found to be capable of influencing the wind circulation in the polar stratosphere by modifying the large-scale Rossby waves, because of the compensation between the forcing of OGWs and that of Rossby waves [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the impacts of different components of SOD on the East Asia summer monsoon circulation and precipitation are robust, for example, upper-level GWD, which is confirmed by running another sensitivity experiment with the upper-level GWD only (not shown). Xu et al (2019), the model horizontal resolution is set to 1°× 1°, with 41 levels in the vertical. The model top is placed at 10 hPa, accompanied with a sponge layer in the uppermost 5 km to damp the waves reflected from the model top.…”
Section: Setup Of Numerical Experimentsmentioning
confidence: 99%
“…It is well known that gravity waves play an important role at lower levels of the atmosphere and influence weather and meteorological phenomena [10]. Some studies demonstrated the importance of applying gravity wave models to improve the accuracy of weather forecast and global circulation models [11,12].…”
Section: Introductionmentioning
confidence: 99%